2006
DOI: 10.1111/j.1574-695x.2006.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in tuberculosis patients and healthy subjects in response to complex and single antigens ofMycobacterium tuberculosis

Abstract: Peripheral blood mononuclear cells (PBMC) were obtained from tuberculosis (TB) patients and Mycobacterium bovis bacillus Calmette-Guerin vaccinated healthy subjects. PBMC were tested for secretion of tumor necrosis factor-alpha (TNF-alpha), interferon-gamma (IFN-gamma), interleukin-5 (IL-5) and IL-10 in response to complex (whole cells, culture filtrate and cell walls), single secreted (Ag85B, ESAT6, MPT64, PstS and MPT70) and single cytosolic (DnaK, GroES and GroEL) antigens of Mycobacterium tuberculosis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 39 publications
10
44
0
1
Order By: Relevance
“…S1 in the supplemental material). In addition, ProPred identified 11 T-cell epitope regions of 9 to 24 residues in length, which were scattered throughout the MPT83 sequence, i.e., amino acids 4 2/9 0/9 0/9 0/9 0/9 7/9 9/9 1/9 0/9 4/9 3/9 9/9 DRB1.7 2/2 0/2 0/2 0/2 0/2 2/2 0/2 0/2 0/2 0/2 0/2 2/2 DRB1. 8 6/6 5/6 1/6 4/6 0/6 0/6 4/6 1/6 0/6 6/6 1/6 6/6 DRB 9/9 7/9 0/9 0/9 1/9 0/9 4/9 0/9 0/9 8/9 8/9 9/9 DRB1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 in the supplemental material). In addition, ProPred identified 11 T-cell epitope regions of 9 to 24 residues in length, which were scattered throughout the MPT83 sequence, i.e., amino acids 4 2/9 0/9 0/9 0/9 0/9 7/9 9/9 1/9 0/9 4/9 3/9 9/9 DRB1.7 2/2 0/2 0/2 0/2 0/2 2/2 0/2 0/2 0/2 0/2 0/2 2/2 DRB1. 8 6/6 5/6 1/6 4/6 0/6 0/6 4/6 1/6 0/6 6/6 1/6 6/6 DRB 9/9 7/9 0/9 0/9 1/9 0/9 4/9 0/9 0/9 8/9 8/9 9/9 DRB1.…”
Section: Resultsmentioning
confidence: 99%
“…Antigen-and peptideinduced proliferation of PBMCs was performed by using standard procedures (4). In brief, PBMCs (2 ϫ 10 5 cells/well) suspended in 50 l of complete tissue culture medium were seeded into the wells of 96-well tissue culture plates (Nunc, Roskilde, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…The memory B cell response in BCG-vaccinated individuals have been shown to be present even 45 years following vaccination [19]. Yet this response, which may initiate clearance, is not sufficient to prevent infection of the individual [15,25,26].…”
Section: The Immune Response To Mtbmentioning
confidence: 99%
“…There is evidence to suggest that the stunting of the humoral response may be due to exposure to other environmental mycobacterial [ [28] have shown that while there is an initial antibody response to these antigens, the next steps involving the complement pathway are suppressed. In addition, Espitia et al [15], Al-Attiyah et al [26] and Rennie et al [25] have shown that antibodies to the Ag85 complex and other environmental mycobacteria can be found in the sera of subjects with no prior Mtb exposure. Furthermore, this presentation does not protect the individual from infection [9].…”
Section: Evading the Humoral Responsementioning
confidence: 99%
“…Although, these genes have only 10-35% homology to esat6, they are approximately of the same size (ca 100 aa) and share a similar genomic organization. Because of the immunodominance of ESAT-6 (ESXA) [12][13][14][15][16][17][18], other ESAT-6 family proteins have also received considerable attention for immunological evaluation [19][20][21]. As given below, the genes of some of these proteins are present in M. tuberculosis-specific genomic regions, and therefore they have been considered useful in the diagnostic and vaccine applications [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%